Terpenes solubility in water and their environmental distribution - Martins, Mónia A.R. (2018)
Terpenes and terpenoids belong to the largest and most diverse class of natural products. Due to the increasing importance of their applications and the emerging perception of their impact on the environment, the available physico-chemical characterization is insufficient. In this work the water solubility of geraniol, linalool, DL-citronellol, thymol, eugenol, carvacrol and p-cymene, in the temperature range from (298.15 to 323.15) K, and at atmospheric pressure, is studied. Due to the low solubility of these compounds a novel technique was adopted for their measurements and validated using the aqueous solubility data for sparingly soluble aromatic compounds. The thermodynamic properties of solution were derived from the experimental data at infinite dilution. It is shown that the solubility of terpenes in water is an endothermic process confirming the existence of UCST phase diagrams, and only for carvacrol and eugenol is entropically driven. The experimental information is shown in a two-dimensional chemical space diagram providing indications to their probable distribution in the environment once released.